ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VII SMP NEGERI 4 CIBINONG MATERI BENTUK ALJABAR DENGAN PROBLEM BASED LEARNING - Sri Soniawati (IKIP Siliwangi, 2022)
Academic achievement of students of SMP Negeri 4 Cibinong in Mathematics for the 2021-2022 academic year using the Problem Based Learning learning model is not satisfactory. This proves that students still do not understand the stages in working on the questions. Another reason is that students are still not familiar with the PBL method compared to conventional methods. The aim of this research is to analyze the level of ability of students when they solve problems, especially in mathematics problems with algebraic material through the use of Problem based learning models. This research method is descriptive and aims to present a sign, phenomenon, or event in the present. Through descriptive research, researchers describe events and events that have a role as center and attention. The result that can be taken is the low problem-solving ability of students at SMP Negeri 4 Cibinong. There are several types of errors when solving problems in algebraic material. 46% ability to understand problems, 40% ability to make plans, and 0% ability to complete plans 16% ability to recheck solutions. Usually students with conventional learning result in students depending on educators or teachers then they experience a decline to solve problems. If the teacher familiarizes the Problem Based Learning learning model, students' problem-solving abilities will increase and learning will not be teacher-centered.